The system of the didactic principles with applicability in teaching economics - TASCOVICI, Daliana Ecaterina; DRAGOMIR, Robert Gabriel (Annals of Spiru Haret University. Economic Series, 2011)
The present paper aims to present the system of didactic principles and offer several models of didactic tasks used in teaching Economic objects, but they can be broaden to any other school objects, in accordance with the presented approaches and their specific features. Thus, we presented the following principles: the principle of the active and conscious appropriation of the knowledge and skills; the intuition principle or of the unity between real and abstract, between rational and sensorial; the principle of accessibility and of respecting the students’ age and individual particularities; the principle of connecting theory with practice; the principle of knowledge systematization and continuity; the principle of the rigorous and durable appropriation of the knowledge, abilities and skills; the principle of assuring the feed-back within the system of learning. The didactic tasks are found after every above mentioned principle. The work is suitable for mainly probationer students and for teachers.